Studying Mothers' Knowledge and Perceptions of Adolescent Reproductive Health - Hartaty, Diana; Martha, Evi (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
This article has been corrected Please see the: https://wmmjournal.org/index.php/wmm/announcement/view/4